The Influence of Brand Ambassador, Brand Image, and Brand Trust on Repurchase Intention (Study on Generation Z Consumers of Skintific Products in Cirebon) - Isma Nurul Khotimah; H. Misbak (Danadyaksa: Post Modern Economy Journal, 2026)
The rapid growth of the skincare industry has intensified competition among brands, compelling companies to adopt effective marketing strategies to drive consumer repurchase intention. Skintific, as one of Indonesia's growing skincare brands, leverages brand ambassadors, builds brand image, and enhances consumer trust to maintain customer loyalty. However, the extent to which these factors influence repurchase intention among Generation Z consumers remains underexplored. This study therefore aims to analyze the influence of brand ambassador, brand image, and brand trust on repurchase intention among Generation Z consumers of Skintific skincare products in Cirebon City. A quantitative approach with explanatory research method was employed. Data were collected through an online questionnaire distributed to 100–150 respondents selected via purposive sampling. Data analysis was conducted using Structural Equation Modeling–Partial Least Squares (SEM-PLS) with SmartPLS software. Results indicate that brand ambassador, brand image, and brand trust each exert a positive and significant influence on repurchase intention, both simultaneously and partially. Among the three variables, brand ambassador demonstrates the most dominant effect. These findings suggest that an effective brand ambassador strategy, supported by a positive brand image and high consumer trust, can significantly increase the repurchase intention of Generation Z consumers toward Skintific skincare products.